More than just hitchhikers: a survey of bacterial communities associated with diatoms originating from sea turtles. Issue 10 (7th September 2022) - Filek, Klara; Lebbe, Liesbeth; Willems, Anne; Chaerle, Peter; Vyverman, Wim; Žižek, Marta; Bosak, Sunčica
Abstract: Diatoms and bacteria are known for being the first colonizers of submerged surfaces including the skin of marine reptiles. Sea turtle carapace and skin harbor diverse prokaryotic and eukaryotic microbes, including several epizoic diatoms. However, the importance of diatom-bacteria associations is hardly investigated in biofilms associated with animal hosts. This study provides an inventory of diatoms, bacteria and diatom-associated bacteria originating from loggerhead sea turtles using both metabarcoding and culturing approaches. Amplicon sequencing of the carapace and skin samples chloroplast gene rbcL and 16S rRNA gene detected, in total, 634 diatom amplicon sequence variants (ASVs) and 3661 bacterial ASVs, indicating high diversity. Cultures of putative epizoic and non-epizoic diatoms contained 458 bacterial ASVs and their bacterial assemblages reflected those of their host. Diatom strains allowed for enrichment and isolation of bacterial families rarely observed on turtles, such as Marinobacteraceae, Alteromonadaceae and Alcanivoracaceae . When accounting for phylogenetic relationships between bacterial ASVs, we observed that related diatom genera might retain similar microbial taxa in culture, regardless of the turtle's skin or carapace source. These data provide deeper insights into the sea turtle-associated microbial communities, and reveal the potential of epizoic biofilms as a source of novel microbes and possibly important diatom-bacteria associations. Abstract : Sea turtles harbor diverse diatom and bacterial assemblages on their carapace and skin, while isolated and cultivated diatom strains retained bacterial communities whose composition reflected the source-host microbiota and diatom genus.